The Completeness and accuracy of clinical coding for diagnosis and medical procedure on the INA-CBGs claim amounts at a hospital in South Jakarta - Cicih Opitasari; Atik Nurwahyuni (Health Science Journal of Indonesia, 2018)
Abstrak Latar belakang: Kelengkapan resume dan ketidaktepatan koding masih menjadi penyebab terbesar pengembalian berkas klaim dari BPJS. Penelitian ini bertujuan untuk melakukan analisis kelengkapan dan ketepatan koding diagnosis dan prosedur terhadap besaran klaim di satu rumah sakit (RS) Pemerintah di Jakarta Selatan. Metode: Penelitian observasional yang dilakukan dengan penelusuran rekam medis (RM) bulan November 2017 dan wawancara mendalam terhadap 7 informan yang terdiri dari manajemen, koder, dokter penanggung jawab pasien (DPJP) dan verifikator RS. Ketepatan koding didapatkan dengan membandingkan pengkodean oleh koder RS dan koder standar. Analisis data dilakukan dengan analisis konten. Hasil: Dari 105 sampel rekam medis didapatkan angka ketidaklengkapan resume terbanyak pada pemeriksaan penunjang (12,2%), ketidaksesuaian pengisian pada diagnosis sekunder mencapai 68,6% dan ketidaktepatan koding paling tinggi pada diagnosis utama (21,9%). Rerata klaim INA-CBGs yang dihasilkan koder RS lebih rendah dari koder standar dengan selisih klaim sebesar 4%. Hal tersebut disebabkan adanya ketidakpatuhan dokter dan tidak semua dokter mendapatkan pelatihan pengkodean. Proses pencatatan RM masih banyak didelegasikan kepada residen. Pemeriksaan resume oleh verifikator dan pengkodean oleh koder masih kurang pemahaman tentang diagnosis dalam konsep INA-CBGs. Kesimpulan: Ketidaklengkapan resume dan ketidaktepatan koding di RS menyebabkan klaim INA-CBGs yang diterima lebih rendah rata-rata 4% sehingga dapat mengurangi pendapatan RS. (Health Science Journal of Indonesia 2018;9(1):14-8) Kata kunci: Ketidaktepatan koding, diagnosis dan prosedur, klaim rendah Abstract Background: Coding inaccuracy and inadequate physician documentation are still the major problem of BPJS claims that resulting potential loss of hospital finance. This study aims to analyze the completeness and accuracy of diagnosis and procedure coding on the INA-CBGs claim amounts at one government hospital in South Jakarta. Methods: This observational study was conducted through medical record review during the period of November 2017 and in-depth interview involved 7 informants consist of hospital management, coders, responsible physicians and hospital verifiers. Re-coding was carried out by standar coder and the results were compared with hospital coders outcome. Content analysis was used to analyze the data. Results: The review of 105 medical record found incomplete documentation for supporting medical examination variable (12.2%), inconsistency documentation of secondary diagnoses were the highest, at 68.6% and the most frequent for inaccurate coding was primary diagnoses at 21.9%. The claims generated by hospital coders are lower than standard coder by an average 4%. The indepth interview revealed low physicians compliance on the documentation standard procedure and lack of coding training for physician. The process of the documentation practice was still delegated to the resident physicians. The discharge summary review by verifier and coding by the coders was still lack of understanding of the diagnosis in the INA-CBGs concept. Conclusion: Incomplete discharge summary and inaccurate coding of diagnosis and procedure generate loss of hospital revenue by an average 4%. (Health Science Journal of Indonesia 2018;9(1):14-8) Keywords: Inaccuracy of clinical coding, diagnosis and procedure, lower claim